(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The level of civilization of a country can be judged by the status of women enjoy in that society and the extent of their participation in the societal process. In spite of rapid urban growth and several development programmes, specific to women and weaker section of people has been initiated throughout the country but the impact of these programmes and policies are far from expectation and the real fruit of development is untouched to the majority of people staying in the rural areas due to lack of proper platforms to develop their capacities and capabilities. Self Help Groups (SHGs) is such an organization of poor people, particularly of women through which they can become self-reliance and self-sufficient to take active part in decision making process in their day-to-day life. Hence, the need of the hour is to extend exhaustive support with the active involvement of both Government and NGOs for challenging poverty as well as empowering women to become self-sufficient in near future.